Place & distance tracker: SAPOD / Syaid M. Asyraf Syaid Mohd - Syaid Mohd, Syaid M. Asyraf (College of Creative Arts, Universiti Teknologi MARA Kedah Branch, 2022)
Post COVID-19 condition, also known as "long COVID," refers collectively to the constellation of long-term symptoms that some people experience after they have had COVID-19. People who experience post COVID-19 conditions sometimes refer to themselves as "long-haulers". SAPOD is a place tracker product that specializes in prioritizing people who have symptoms on Covid-19. The main focus of this product is designed to help manufacturing workers from going through red zone areas. Furthermore, this product is also used to let the management easier track the manufacturing workers' movement in the factory. The objectives of SAPOD are to reduce covid cases from factories, to let people know which place is in a red zone, and to track the movement of workers in factories. With this potential product, Designer hopes it can improve health safety from covid-19 disease. The benefit that can be obtained while using this product is that it makes it easier for users to be more careful when in dangerous places. It is also designed to look attractive and stylish with the ergonomic shape applied in the product. This can make it not only factory workers but many more people regularly use this product.